Embedded timing and alert device triggered by total dissolved solids (TDS) for monitoring disinfection duration in acidic electrolyzed oxidizing water - Wei Zheng; Hongxia Xu; Yuan Mao; Fucheng He; Ping Gui (PLoS ONE, 2026)
To address the absence of a reliable timing and alerting tool for acidic electrolyzed oxidizing water (AEOW) disinfection of medical instruments in the Central Sterile Supply Department (CSSD), we developed an embedded timing and alert device triggered by total dissolved solids (TDS) sensing. Built around an Arduino development board, the device integrated a TDS sensor module, a rechargeable battery, and a wireless charging coil. Encapsulated with potting adhesive, it achieved an IP67 protection rating. It can identify the AEOW environment through TDS value detection to automatically start/stop timing, and is equipped with features including light alerts, data storage, and traceability. Medical instruments disinfected with AEOW in the CSSD of a hospital were selected as the test objects. Digital kitchen timers were used as the control group in September 2025, and TDS-triggered timers were adopted as the experimental group in October 2025. A comparative analysis was conducted on the disinfection timing execution rate and disinfection duration compliance rate between the two groups. The results demonstrated that the disinfection timing execution rate of 94.92% (655/690) and the disinfection duration compliance rate of 98.26% (678/690) in the experimental group were higher than those of 84.88% (713/840) and 93.69% (787/840) in the control group, with statistically significant differences (P < 0.001). Characterized by low cost and simple operation, the TDS-triggered timer provides a reliable, automated, and traceable timing solution for AEOW disinfection in CSSD. It also facilitates digital management of the disinfection process, and is expected to improve the quality of AEOW disinfection and enhance patient safety.